The association between lymph node status and the tumor size in breast cancer – results from the Danish Breast Cancer Group (DBCG) - Tanja L. Fris; Marianne D. Lautrup; Peer M. Christiansen (Acta Oncologica)
Background and purpose: The association between the tumor size and the risk of lymph node metastasis (LNM) is well known. The purpose of this study is to describe a new model for predicting the occurrence of LNM at an earlier time for breast cancer patients where at a given time this association is known.